2017
DOI: 10.12991/marupj.319204
|View full text |Cite
|
Sign up to set email alerts
|

Protoscolicidal Effects and Acute Toxicity of Essential Oil and Methanolic Extract of Cuminum cyminum Seeds

Abstract: Surgical treatments were the gold standard for treatment of cystic echinococcosis (CE) until the last 30 years. Existing scolicidal agents such as hypertonic saline and silver-nitrate which have been used for inactivation of protoscoleces during surgery are associated with some serious adverse effects. The present study was designed to investigate in vitro scolicidal activity of Cuminum cyminum L. against protoscoleces of hydatid cysts and its acute toxicity in mice model. Protoscoleces were aseptically aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…They revealed that C cyminum essential oil at a concentration of 50 and 25 μL/mL and the methanolic extract at concentrations of 100 and 50 mg/mL killed 100% protoscolices after exposure for 10 and 20 minutes, respectively. 28 In the present study, methanol extract of S perfoliata, at the concentration of 0.1, 0.2 and 0.4 mg/mL at different exposure periods showed significant scolicidal activity. At the end of the work there was no sufficient protoscolices to continue for more concentrated extract.…”
Section: F I G U R Ementioning
confidence: 46%
“…They revealed that C cyminum essential oil at a concentration of 50 and 25 μL/mL and the methanolic extract at concentrations of 100 and 50 mg/mL killed 100% protoscolices after exposure for 10 and 20 minutes, respectively. 28 In the present study, methanol extract of S perfoliata, at the concentration of 0.1, 0.2 and 0.4 mg/mL at different exposure periods showed significant scolicidal activity. At the end of the work there was no sufficient protoscolices to continue for more concentrated extract.…”
Section: F I G U R Ementioning
confidence: 46%
“…Several plant extracts have been tested in vivo against CE and revealed high efficacy; however, only a few essential oils were used. The commonly tested essential oils against CE in vivo include carvacrol [ 59 ], β-myrcene [ 6 ] essential oils, Cuminum cyminum seeds [ 60 ], and Zataria multiflora [ 13 , 61 ], Zingiber officinale [ 43 ], Allium sativum [ 62 ], Punica granatum peel [ 10 ], and Ziziphora tenuior [ 63 ] plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, N.sativa seeds oil has an effective antimicrobial activities considering their low coasty and good safety products (37). Agrawal et al (38) manifested significant N. sativa seed's oil antihelmintic activity against some pathogenic nematode and cestode.…”
Section: Discussionmentioning
confidence: 99%